2021
DOI: 10.7759/cureus.16603
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 Vaccine in Pakistan: A Nationwide Cross-Sectional Study

Abstract: The coronavirus disease 2019 (COVID-19) vaccine is available across various countries worldwide, with public-private partnerships ensuring all individuals are vaccinated through a phased approach. Irrespective of the geographical spread, several myths pertaining to the COVID-19 vaccine have stemmed, ultimately limiting the national administration of vaccines and rollouts. This study assessed the acceptance of the COVID-19 vaccine among the general public in Pakistan. MethodsA pre-validated questionnaire was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…Another study approximates vaccine acceptance rate to be 70% in the population of Pakistan [29]. This study also reports a quite similar finding of HCWs/doctors being the most reliable source of information in view of the respondents.…”
Section: Discussionsupporting
confidence: 77%
“…Another study approximates vaccine acceptance rate to be 70% in the population of Pakistan [29]. This study also reports a quite similar finding of HCWs/doctors being the most reliable source of information in view of the respondents.…”
Section: Discussionsupporting
confidence: 77%
“…Even global data favors higher education for vaccination acceptance [9,[21][22][23]. Similarly, as seen around the world and in a study from Pakistan, employed participants and especially those related to medical fields were found to be more welcoming to COVID-19 vaccination than their unemployed counterparts [8,17]. In our setup, multiple factors are possibly contributing to it including differences in knowledge, financial status and social communication, and higher frequency of females in the unemployed group.…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, as proven by the past experience of the polio vaccine, Pakistan is at high risk of COVID-19 vaccine resistance [7]. There are studies for COVID vaccination hesitancy from around the world and a couple of studies from Pakistan [6][7][8][9][10][11]17,18]. But most of them are likely biased by the comparatively literate responder to their online surveys, the method used in most such studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study by Aga Khan University on vaccination acceptance rates showed 66.8% positive attitude towards COVID-19 vaccination (11). It identi ed factors such as information from media sources, people's trust in the government and history of having contracted the virus (12).…”
Section: Introductionmentioning
confidence: 99%